Pearl Millet Inbred and Testcross Performance under Low Phosphorus in West Africa. Issue 6 (1st November 2014) - Gemenet, Dorcus C.; Hash, C. Tom; Sy, Ousmane; Zangre, Roger G.; Sanogo, Moussa D.; Leiser, Willmar L.; Parzies, Heiko K.; Haussmann, Bettina I.G.
ABSTRACT: Pearl millet [ Pennisetum glaucum (L.) R. Br] is a food security crop for millions living in drylands of Africa and Asia. Its production on acid sandy soils of the Sahel is limited by erratic rainfall and poor soil fertility, especially low P soils. We sought to elucidate the genetic variation in West and Central African landrace‐derived inbred lines for grain yield under low P conditions, to determine their performance as inbred lines per se and in hybrid combinations, and to determine quantitative‐genetic parameters to derive an appropriate breeding strategy to enhance grain yield under low P conditions. We evaluated a total of 155 landrace‐derived inbred lines as well as their testcrosses in four locations during two years under two treatments, high P (HP; with P fertilization) and low P (LP; without P fertilization). Results revealed significant effects for genotypes, P‐level, genotype × P‐level, as well as genotype × environment interactions. Grain yield reductions under LP treatment ranged from 7.9 to 35.5%, and 11.2 to 60.9% for inbred lines and testcrosses respectively, with positive midparent heterosis averaging 43.5% under LP. We conclude that direct selection of testcrosses under LP is more effective and that indirect selection for testross performance from inbred line performance is not desirable.